2019
DOI: 10.1177/0960327119867758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infliximab against carbon tetrachloride-induced intestinal injury via lipid peroxidation and apoptosis

Abstract: Carbon tetrachloride (CCL4) is often employed in the production of chlorofluorocarbons, petroleum refining, oil and rubber processing, and laboratory applications. Oral, subcutaneous, and inhalation exposure to CCL4 in animal studies have been shown to be capable of leading to various types of cancer (benign and malignant, liver, breast, and adrenal gland tumors). The present study also evaluated the protective role of infliximab (INF) against the deleterious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…The ndings showed that continuous cold stimulation induces an increase in HSP70 protein expression but not HSP90. It has been suggested that an essential indicator of intestinal injury is the apoptosis of intestinal epithelial cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…The ndings showed that continuous cold stimulation induces an increase in HSP70 protein expression but not HSP90. It has been suggested that an essential indicator of intestinal injury is the apoptosis of intestinal epithelial cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…The drug's inability to differentiate between sTNF and tmTNF poses challenges, inhibiting baseline activity and causing adverse effects [69]. Exogenous TNF blockers, including etanercept, may increase the risk of serious infections and cancer according to a meta-analysis of clinical trials comparing TNF-binding medications like etanercept and infliximab [73]. Etanercept, in placebo-controlled trials, demonstrated a 35% infection rate over the therapy course, associated with serious bacterial, viral, and fungal infections [69].…”
Section: Tnf As a Therapeutic Targetmentioning
confidence: 99%
“…It was shown to result in histopathological findings such as vascular congestion, infiltration, and vacuolar degeneration in cells in the liver (1). Moreover, it induces oxidative damage by increasing the amounts of malondialdehyde (MDA), which is an oxidative stress marker, in the intestine and the lung, as well as increasing the number of cells marked by the TUNEL method, which indicates necrotic cells (5,6).…”
Section: Introductionmentioning
confidence: 99%